Bacterial and Pneumocystis Infections in the Lungs of Gene-Knockout Rabbits with Severe Combined Immunodeficiency - Song, Jun; Wang, Guoshun; Hoenerhoff, Mark J.; Ruan, Jinxue; Yang, Dongshan; Zhang, Jifeng; Yang, Jibing; Lester, Patrick A.; Sigler, Robert; Bradley, Michael; Eckley, Samantha; Cornelius, Kelsey; et al. (Frontiers in Immunology, 2018)
Using the CRISPR/Cas9 gene editing technology, we recently produced a number of rabbits with mutations in immune function genes, including FOXN1, PRKDC, RAG1, RAG2 and IL2RG. Seven founder knockout rabbits (F0) and three male IL2RG null (-/y) F1 animals demonstrated severe combined immunodeficiency (SCID), characterized by absence or pronounced hypoplasia of the thymus and splenic white pulp, and absence of immature and mature T and B-lymphocytes in peripheral blood. Complete blood count (CBC) analysis showed severe leukopenia and lymphocytopenia accompanied by severe neutrophilia. Without prophylactic antibiotics, the SCID rabbits universally succumbed to lung infections following weaning. Pathology examination revealed severe heterophilic bronchopneumonia caused by Bordatella bronchiseptica in several animals, but a consistent feature of lung lesions in all animals was a severe interstitial pneumonia caused by Pneumocystis oryctolagi. which was confirmed by histological examination and PCR analysis of Pneumocystis genes. The results of this study suggest that these SCID rabbits could serve as a useful model for human severe combined immunodeficiency to investigate the disease pathogenesis and development of gene and drug therapies.